(untitled) (Journal of Hama University, 2023)
This research aims to identify the relationship between moral intelligence and the level of ambition and to identify the differences between last year students in the Faculty of Education at the University of Damascus in moral intelligence and the level of ambition according to the variable of specialization (psychology, class teacher) and the variable of sex (male and female). The research sample consisted of (304) male and female final year students in the College of Education at the University of Damascus, divided into (126) psychology and (178) class teachers, who were selected in a stratified random manner from the College of Education at the University of Damascus, and a measure of the level of ambition prepared by Moawad was applied to them. and Abdel-Azim (2005), and the measure of moral intelligence was prepared by the researcher after she applied it to an exploratory sample and made sure of its validity and reliability. The search results indicated: - There is a statistically significant positive correlation between moral intelligence and the level of ambition among the research sample, and the correlation value was (0.72). - There are no statistically significant differences between the study specialization in psychology and the class teacher in moral intelligence. - There are statistically significant differences between the academic specialization of psychology and a class teacher in the level of ambition in favor of psychology students. - There are statistically significant differences between the male and female sexes in moral intelligence in favor of females. - There are statistically significant differences between males and females in the level of ambition in favor of males.